Variation and Non-formal Classification of Indonesian Eggplant (Solanum melongena L.) Accessions Based on Macro and Micro-morphological Characters - Uni Baroroh Husnudin; Suharyanto Suharyanto; Budi Setiadi Daryono; Purnomo Purnomo (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2019)
Indonesia has a variety of eggplant germplasms and is considered as one of the largest producing countries in the world. The study was conducted to assess the variation of 21 accessions and 2 commercial cultivars of eggplant from Indonesia based on 30 macromorphological and 8 leaves micromorphological characters. Cluster analysis was conducted by UPGMA (Unweighted Pair Group Methods with Arithmetic averages) to create a dendrogram and construct eggplants grouping. PCA (Principal Component Analysis) was also performed to define the role of each character in the group by using MVSP (Multivariate Statistical Program) v.3.1 software. Results showed that eggplant accessions have macromorphological variation in fruit curvature, fruit shape, fruit apex, and fruit color, as well as leaves micromorphological characters such as the epidermal wall, trichome shape, and stomata type. Dendrogram based on macromorphological characters divided the accessions into 2 groups: curved and non-curved fruit groups. The non-curved fruit group divided into more spiny and less spiny leaves sub groups. Dendrogram based on leaves micromorphological characters divided the accessions into 2 groups based on the epidermal wall, trichome shape, and stomata type. Eggplant grouping doesn’t occur based on the origin of collection areas indicating that its variability isn’t affected by the environment.